Preparation method and hydrogenation application of Pd-Ru synergistic catalyst based on metal organic framework

Through the Pd-Ru synergistic catalyst based on the metal organic framework, the problem of poor selectivity in the selective hydrogenation process of alkynes is solved, high conversion and high selectivity are achieved, and the good stability of the catalyst is demonstrated.

CN119608153AActive Publication Date: 2025-03-14LIAOCHENG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411830075.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The prior art has poor selectivity in the selective hydrogenation process of alkynes, resulting in excessive hydrogenation to produce by-products.

Method used

Using a Pd-Ru synergistic catalyst based on a metal organic framework, Pd-Ru@ZIF-8 was prepared, silica coating was performed, and then carbonization reduction was performed.

Benefits of technology

Under mild reaction conditions, high conversion rate (95.3%) and high selectivity (99.4%) of phenylacetylene were achieved, and the activity and selectivity of the catalyst were kept unchanged through five cycles of reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608153A_ABST
    Figure CN119608153A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Pd-Ru synergistic catalyst based on a metal organic framework (MOF) and hydrogenation application of the Pd-Ru synergistic catalyst. On the basis of an MOF material, hydrolysis of Pd-Ru alloy and tetraethyl orthosilicate is coordinated through a one-pot method, and then the metal organic material coated Pd-Ru synergistic catalyst PdRu / C coated SiO2 is synthesized through high-temperature carbonization reduction in a nitrogen atmosphere; the catalyst can be used for preparing olefin through alkyne selective hydrogenation. Compared with pure palladium or pure ruthenium, the catalyst provided by the invention can effectively reduce the desorption energy of styrene, limits excessive hydrogenation of styrene, and realizes high conversion rate (95.3%) and high selectivity (99.4%) of phenylacetylene under mild reaction conditions. Meanwhile, the catalyst has excellent catalytic stability and relatively good universality, and has a very good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of chemical synthesis, and in particular to a Pd-Ru synergistic catalyst based on a metal organic framework, a preparation method thereof and application in selective hydrogenation. Background Art

[0002] Selective hydrogenation of alkynes to olefins plays a vital role in the synthesis of fine chemicals. However, over-hydrogenation is prone to occur during the reaction, which inevitably produces by-products such as alkanes.

[0003] As we all know, the hydrogenation process of phenylacetylene (PA) is a simple cascade process. The intermediate reaction will produce styrene (SM), which is the main raw material for the production of polymer materials such as resin (ABS) industry, polystyrene (PS) industry and styrene-butadiene rubber (SBR) industry. In recent years, many research results have been born, such as various Pd-based nanocatalysts, but styrene will be further converted into ethylbenzene (EB), which is a saturated product. As a result, many scholars have made many studies on the purification and separation of styrene production, among which Pd-based nanocatalysts [1-2] Due to its excellent hydrogenation performance, it is the most commonly used catalyst for the selective hydrogenation of phenylacetylene, but its low selectivity still leads to over-hydrogenation of phenylacetylene.

[0004] In current use, the preparation process of Pd nanocatalysts is often improved, or they are compounded with other metals, co-catalysts and other active components to make them have better performance. [3] It shows that Ru can show good catalytic activity in the catalyst and maintain a certain selectivity. On this basis, in recent years, some scholars have applied the Pd-Ru synergistic catalytic system to the catalytic hydrogenation of phenylacetylene, which greatly improved the selectivity for styrene while maintaining a high conversion rate. This catalytic activity is attributed to the synergistic effect of the Pd-Ru single point, which reduces the desorption energy of styrene and thereby increases the barrier for further hydrogenation of styrene, making it possible to apply the Pd-Ru synergistic catalytic system to the hydrogenation of phenylacetylene.

[0005] Metal-organic frameworks (MOFs) are a class of porous materials assembled by the coordination of metal ions and organic matter. [4] Due to its fine, adjustable and uniform pore structure, MOFs have become an ideal material for coating the surface of metal nanoparticles and can prevent the loss and peeling of nanometal particles during the reaction. In addition, MOF materials have more unsaturated sites, which are conducive to the adsorption of substrates, thereby significantly improving the catalytic effect of catalysts. Therefore, metal organic frameworks are of great significance to catalytic reactions.

[0006] Therefore, there is an urgent need to develop new catalysts with high selectivity and activity for the selective hydrogenation of alkynes (such as phenylacetylene).

[0007] References

[0008] [1]Sabrina Ballauri,Enrico Sartoretti,et al.Praseodymium doping inceria-supported palladium nanocatalysts as an effective strategy to minimize the inhibiting effects of water during methane oxidation[J].A.Catalysis B:Environmental 320(2023)121898.

[0009] [2]Md.Lutfor Rahman,Mohd Sani Sarjadi,et al.Silica-coated magneticpalladium nanocatalyst for Suzuki-Miyaura cross-coupling[J].A.Journal ofChemistry(2022)15,103983.

[0010] [3]Wenqian Yang, Qinglin Liu, Jun Yang, et al.Ultrafifine PdRuNanoparticles Immobilized in Metal-Organic Frameworks for EfficientFluorophenol Hydrodeflfluorination under Mild Aqueous Conditions[J].CCSChem.2022,4,2276-2285.

[0011] [4]Annemieke Janssen,Yifeng Shi,et al.Separating Growth fromNucleation for Facile Control over the Size and Shape of PalladiumNanocrystals[J].Chemistry-A European 202001626.

[0012] [5]Haiping Li,Tianxing Yang,et al.Synthesis of supported Pdnanocluster catalyst by spontaneous reduction on layered double hydroxide[J].J.of Catalysis 385(2020)313-323.

[0013] [6]Qianqian Xie,Chao Lei,et al.Mesoporous ferrihydrite-supported Pdnanoparticles for enhanced catalytic dehalogenation of chlorinatedenvironmental pollutant[J].J.of Colloid and Interface Science 608(2022)2907-2920.

[0014] [7]Ming Zhang, Chaohai Wang, Chao Liu, et al. Metal-organic framework derived Co3O4 / C@SiO2yolk-shell nanoreactors with enhanced catalytic performance [J]. J.Mater.Chem.A, 2018, 6, 11226. Summary of the invention

[0015] The technical problem to be solved by the present invention is to provide a Pd-Ru synergistic catalyst based on a metal organic framework, a preparation method thereof and an application thereof in selective hydrogenation in view of the deficiencies in the above-mentioned prior art.

[0016] In order to solve the above technical problems, the technical solution adopted by the present invention is: in the first aspect of the present invention, a method for preparing a Pd-Ru synergistic catalyst based on a metal organic framework is provided, comprising the following steps:

[0017] S1. Preparation of Pd-Ru@ZIF-8:

[0018] Pd 2+ 、Ru 3+ 、Zn 2+ , 2-methylimidazole in a solvent, stirred for reaction, centrifuged after the reaction was completed, and the solid product was collected to obtain Pd-Ru@ZIF-8;

[0019] S2, coating Pd-Ru@ZIF-8 with silicon dioxide to prepare PdRu@ZIF-8@SiO2;

[0020] S3, carbonization reduction to prepare PdRu / C@SiO2, that is, the Pd-Ru synergistic catalyst based on the metal organic framework.

[0021] Preferably, step S1 specifically comprises:

[0022] S1-1, add 2.5-10 mg Pd(Acac)2 and 17.5-70 mg Ru(Acac)3 into 10-50 mL of a methanol mixed solution containing 280-1120 mg Zn(NO3)2·6H2O, mix well, and obtain a mixed solution A;

[0023] S1-2, adding 263-1052 mg of 2-methylimidazole to 10-50 mL of methanol, and dispersing by ultrasonication to obtain a mixed solution B;

[0024] S1-3. Add mixed solution B to mixed solution A, and stir to react for 12-48 hours. After the reaction is completed, collect the solid product by centrifugation, wash with methanol, and dry to constant weight to obtain Pd-Ru@ZIF-8.

[0025] Preferably, step S2 specifically comprises:

[0026] Take the Pd-Ru@ZIF-8 prepared in step S1 and add it to the ethanol aqueous solution, mix it evenly, add ammonia water, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate in sequence, stir to react, after the reaction is completed, centrifuge and wash the product, collect the solid product, dry to constant weight, and grind to obtain PdRu@ZIF-8@SiO2.

[0027] Preferably, step S2 specifically comprises:

[0028] Take 10-40g of Pd-Ru@ZIF-8 prepared in step S1 and add it to 10-40mL of ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, mix well, add 0.5-2mL of ammonia water with a mass concentration of 25%-28%, and then add 250-1000mg of hexadecyltrimethylammonium bromide. After it is completely dissolved, add 25-100μL of tetraethyl orthosilicate, stir and react for 6-24h, wash the product with ethanol solution by centrifugation, collect the solid product, dry it at 50-70℃ to constant weight, grind it, and obtain PdRu@ZIF-8@SiO2.

[0029] Preferably, step S3 specifically comprises:

[0030] Under a nitrogen atmosphere, the PdRu@ZIF-8@SiO2 prepared in step S2 is first calcined at 200-300°C for 240-960min, then heated to 500-700°C, calcined and reduced at 500-700°C for 90-360min, and cooled to room temperature to obtain PdRu / C@SiO2, i.e., the Pd-Ru synergistic catalyst based on the metal organic framework.

[0031] Preferably, the preparation method of the metal organic framework-based Pd-Ru synergistic catalyst comprises the following steps:

[0032] S1. Preparation of Pd-Ru@ZIF-8:

[0033] S1-1, add 5 mg Pd(Acac)2 and 35 mg Ru(Acac)3 into 25 mL methanol mixed solution containing 560 mg Zn(NO3)2·6H2O, mix well, and obtain mixed solution A;

[0034] S1-2, adding 526 mg of 2-methylimidazole into 25 mL of methanol, and dispersing by ultrasonication to obtain a mixed solution B;

[0035] S1-3, adding mixed solution B to mixed solution A, stirring and reacting for 24 hours, after the reaction is completed, collecting the solid product by centrifugation, washing with methanol, drying to constant weight at room temperature, and grinding to obtain Pd-Ru@ZIF-8;

[0036] S2. Pd-Ru@ZIF-8 is coated with silicon dioxide to prepare PdRu@ZIF-8@SiO2:

[0037] Take 20g of the Pd-Ru@ZIF-8 prepared in step S1 and add it to 20mL of an ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, mix well, add 1mL of 25% ammonia water, then add 500mg of hexadecyltrimethylammonium bromide, add 50μL of tetraethyl orthosilicate after it is completely dissolved, stir at room temperature for 12h, wash the product with an ethanol solution by centrifugation, collect the solid product, dry it at 60°C to constant weight, grind it, and obtain PdRu@ZIF-8@SiO2;

[0038] S3, carbonization reduction to prepare PdRu / C@SiO2:

[0039] Under a nitrogen atmosphere, the PdRu@ZIF-8@SiO2 prepared in step S2 was first calcined at 250°C for 480 min, then heated to 600°C, calcined and reduced at 600°C for 180 min, and cooled to room temperature to obtain PdRu / C@SiO2, i.e., the Pd-Ru synergistic catalyst based on the metal organic framework.

[0040] The second aspect of the present invention provides a Pd-Ru synergistic catalyst based on a metal organic framework, which is prepared by the method as described above.

[0041] The third aspect of the present invention provides a use of the Pd-Ru synergistic catalyst as described above in the selective hydrogenation of alkynes to olefins.

[0042] Preferably, the alkyne is any one of phenylacetylene, 2-ethynyltoluene, 3-ethynyltoluene, 4-ethynyltoluene, 4-methoxyphenylacetylene, 4-ethynylaniline, 4-ethylphenylacetylene, 4-ethynylnitrobenzene, 4-fluorophenylacetylene, 4-chlorophenylacetylene, and 4-bromophenylacetylene.

[0043] Preferably, the application method is:

[0044] Evenly mix alkyne, ethanol and Pd-Ru synergistic catalyst, react for 1-4 hours at 65-85°C and 0.5-2MPa in H2 atmosphere to prepare the corresponding olefin;

[0045] Wherein, the mass ratio of alkyne:ethanol:Pd-Ru synergistic catalyst is 5-20:0.5-2:0.5-2.

[0046] The beneficial effects of the present invention are:

[0047] The present invention is based on MOF materials, coordinates the hydrolysis of Pd-Ru alloy and tetraethyl orthosilicate (TEOS) by a one-pot method, and then synthesizes a metal organic material-coated Pd-Ru synergistic catalyst: PdRu / C@SiO2 by high-temperature carbonization reduction under a nitrogen atmosphere. The catalyst can be used for selective hydrogenation of alkynes to prepare olefins.

[0048] Compared with pure palladium or pure ruthenium, the catalyst of the present invention can effectively reduce the desorption energy of styrene, limit the over-hydrogenation of styrene, and achieve a high conversion rate (95.3%) and high selectivity (99.4%) of phenylacetylene under mild reaction conditions; this excellent performance is attributed to the synergistic effect of Pd and Ru single points strongly anchored in the metal organic framework, and the formed alloy hinders the further hydrogenation of styrene. At the same time, after the catalyst undergoes five cycles of reaction, the activity and selectivity of the catalyst remain unchanged, indicating that it has excellent catalytic stability. In addition, this catalyst is applied to the selective hydrogenation reaction of various phenylacetylene derivatives, and all show good activity and selectivity, proving that the catalyst has certain universality and good application prospects. The present invention provides a new idea for the synergistic catalytic system based on single-point active sites for the selective hydrogenation reaction of alkynes. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1Schematic diagram of the synthesis route of PdRu / C@SiO2 and PdRu@SiO2;

[0050] Figure 2 SEM images of PdRu@ZIF-8@SiO2 (a), PdRu@SiO2 (b) and PdRu / C@SiO2 (c) prepared in Example 1;

[0051] Figure 3 XRD patterns of PdRu@ZIF-8@SiO2, PdRu@SiO2 and PdRu / C@SiO2 prepared in Example 1;

[0052] Figure 4 , respectively, are N2 adsorption-desorption curves of PdRu@SiO2 and PdRu / C@SiO2 prepared in Example 1;

[0053] Figure 5 The pore size distribution diagram of PdRu@SiO2 and PdRu / C@SiO2 prepared in Example 1;

[0054] Figure 6 FT-IR images of PdRu@ZIF-8@SiO2, PdRu@SiO2 and PdRu / C@SiO2 prepared in Example 1;

[0055] Figure 7 The test results of the effect of reaction solvent on the performance of selective catalytic hydrogenation of phenylacetylene are shown;

[0056] Figure 8 The test results of the effect of reaction temperature on the performance of selective catalytic hydrogenation of phenylacetylene are shown;

[0057] Fig. 9 The test results of the effect of reaction pressure on the performance of selective catalytic hydrogenation of phenylacetylene are shown;

[0058] Fig.10 The test results of the cyclic application experiment of the PdRu / C@SiO2 catalyst prepared in Example 1 are as follows;

[0059] Fig.11 These are the test results of the effect of reaction time on the catalytic performance of the catalyst after the cycling experiment. DETAILED DESCRIPTION

[0060] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0061] It should be understood that the terms such as “having”, “including” and “comprising” used in the present invention do not exclude the existence or addition of one or more other elements or combinations thereof.

[0062] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0063] 1. The main instruments used in the following examples are shown in Table 1.1:

[0064] Table 1.1

[0065]

[0066]

[0067] 2. The sources of the main chemical reagents used in the following examples are shown in Table 1.2:

[0068] Table 1.2

[0069]

[0070]

[0071] 3. Related performance characterization methods

[0072] X-ray diffractometer (XRD)

[0073] In this study, X-ray powder diffractometer was used to characterize the crystal structure of the catalyst. The test conditions are as follows: the incident radiation is Cu-Kɑ (λ = 0.15406nm, 40kV, 40mA), and the test range is 10°-80°.

[0074] Scanning electron microscopy (SEM)

[0075] The surface area microstructure of the catalysts was analyzed using a field emission scanning electron microscope (SEM, JEOL-6300F, 5 kV).

[0076] N2 adsorption-desorption test

[0077] Before the measurement, the sample was vacuum degassed at 300 °C for 6 h, and then the pore diameter distribution and specific surface area of ​​the catalytic system were calculated using the N2 adsorption-desorption test (BET) method. The pore structure of the catalyst was then analyzed using an automatic adsorption analyzer.

[0078] Fourier Transform Infrared Spectroscopy (FT-IR)

[0079] The infrared spectrometer was used to collect the data, with a spectral range of 400-4000cm-1 .

[0080] Example 1

[0081] A Pd-Ru synergistic catalyst based on a metal organic framework, the preparation method of which comprises the following steps:

[0082] S1. Preparation of Pd-Ru@ZIF-8:

[0083] S1-1, add 5 mg of Pd(Acac)2 (acetylacetonate palladium (II)) and 35 mg of Ru(Acac)3 (acetylacetonate ruthenium (III)) to 25 mL of a methanol mixed solution containing 560 mg of Zn(NO3)2·6H2O, mix well, and obtain a mixed solution A;

[0084] S1-2, adding 526 mg of 2-methylimidazole into 25 mL of methanol, and dispersing by ultrasonication to obtain a mixed solution B;

[0085] S1-3. Add mixed solution B to mixed solution A, stir and react for 24 hours. After the reaction is completed, a red liquid is obtained. The solid product is collected by centrifugation, washed with methanol, and dried to constant weight at room temperature to obtain Pd-Ru@ZIF-8.

[0086] As a control for subsequent experiments, Pd@ZIF-8 and Ru@ZIF-8 were prepared at the same time. The preparation method of Pd@ZIF-8 was the same as above except that Ru(Acac)3 was not added and the addition amount of Pd(Acac)2 was changed to 40 mg. After the reaction in S1-3 was completed, a light yellow liquid was obtained. The preparation method of Ru@ZIF-8 was the same as above except that Pd(Acac)2 was not added and the addition amount of Ru(Acac)2 was changed to 40 mg. 32 The same as above except that the amount of addition was changed to 40 mg, after the reaction in S1-3 was completed, a deep red solution was obtained;

[0087] S2. Pd-Ru@ZIF-8 is coated with silicon dioxide to prepare PdRu@ZIF-8@SiO2:

[0088] Take 20g of Pd-Ru@ZIF-8 prepared in step S1 and add it to 20mL of ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, mix well, add 1mL of 25% ammonia water, then add 500mg of hexadecyltrimethylammonium bromide, add 50μL of tetraethyl orthosilicate after complete dissolution, stir at room temperature for 12h, wash the product by centrifugation with ethanol solution, collect the solid product, dry it at 60°C to constant weight, grind it, and obtain a white product: PdRu@ZIF-8@SiO2.

[0089] As a control for subsequent experiments, Pd@ZIF-8 and Ru@ZIF-8 were used to replace the above Pd-Ru@ZIF-8 to prepare Pd@ZIF-8@SiO2 and Ru@ZIF-8@SiO2 respectively according to the same method as above.

[0090] S3, carbonization reduction to prepare PdRu / C@SiO2:

[0091] Under a nitrogen atmosphere, the PdRu@ZIF-8@SiO2 prepared in step S2 was placed in an ark, first calcined at 250°C for 480 min, then heated to 600°C, calcined and reduced at 600°C for 180 min, and cooled to room temperature to obtain PdRu / C@SiO2, i.e., the Pd-Ru synergistic catalyst based on the metal organic framework.

[0092] As a control for subsequent experiments, two other catalysts were prepared using Pd@ZIF-8@SiO2 and Ru@ZIF-8@SiO2, respectively, instead of the above PdRu / C@SiO2: Pd / C@SiO2 and Ru / C@SiO2.

[0093] In addition, the following three catalysts were prepared for subsequent comparison:

[0094] The PdRu@ZIF-8@SiO2 prepared in step S2 was placed in a crucible, and calcined in a muffle furnace at 400°C in an air atmosphere for 480 min to obtain an off-white powder, labeled as PdO-RuO2@SiO2. Subsequently, the PdO-RuO2@SiO2 was placed in a tubular furnace and fully reduced at 300°C in a H2 atmosphere to obtain the final PdRu@SiO2, and the sample appeared off-white.

[0095] Pd@ZIF-8@SiO2 and Ru@ZIF-8@SiO2 were used to replace the above PdRu@ZIF-8@SiO2. According to the same method as above, two other catalysts were prepared: Pd@SiO2 and Ru@SiO2. All the samples were grayish white.

[0096] Therefore, a total of 6 catalysts were prepared through the above method: PdRu / C@SiO2, Pd / C@SiO2, Ru / C@SiO2; PdRu@SiO2, Pd@SiO2, Ru@SiO2. For subsequent experiments, the last 5 were mainly used for comparison.

[0097] Among them, the synthesis routes of PdRu / C@SiO2 and PdRu@SiO2 are as follows Figure 1 shown.

[0098] Example 2 Performance Characterization

[0099] 1. Reference Figure 2 , respectively, are SEM images of PdRu@ZIF-8@SiO2 (a), PdRu@SiO2 (b), and PdRu / C@SiO2 (c) prepared in Example 1; the SEM image shows that the prepared sample PdRu / C@SiO2 has a rhombic dodecahedral structure. The enlarged SEM image is shown in Figure 2 (c) Insertion shows that the PdRu / C@SiO2 core is obviously wrapped by the silica shell, which indicates that the high-temperature carbonization process retains the dodecahedral structure without any damage.

[0100] Reference Figure 3 , respectively, are the XRD spectra of PdRu@ZIF-8@SiO2, PdRu@SiO2 and PdRu / C@SiO2 prepared in Example 1. It can be seen that all spectra show broad SiO2 diffraction peaks (PDF 29-0085), and no diffraction peaks of single metal Ru, Pd and PdRu alloy are observed. This is mainly due to the highly dispersed and relatively small nanoparticles. For PdRu@ZIF-8@SiO2, there are also typical ZIF-8 crystal plane diffraction peaks, indicating that MOF materials have been obtained. The above materials are further carbonized and reduced at high temperature to obtain PdRu / C@SiO2, which adds eight sharp ZnO crystal plane diffraction peaks (PDF 36-1451), proving the existence of a partial organic metal framework after carbonization.

[0101] Reference Figure 4 , respectively, are the N2 adsorption-desorption curves of PdRu@SiO2 and PdRu / C@SiO2 prepared in Example 1. Both samples show type IV isotherms with obvious hysteresis loops, and are typical mesoporous materials. Figure 5 The pore size distribution diagram of PdRu@SiO2 and PdRu / C@SiO2 shows that there are a small number of micropores below 2nm, and the mesopores of about 5-10nm are dominant. The pores above 20nm correspond to the accumulation pores between the hollow nanocatalysts.

[0102] Table 2.1 Structural characteristics of PdRu@SiO2 and PdRu / C@SiO2

[0103]

[0104]

[0105] Note: a pore volume refers to the total pore volume after single-point adsorption; b average pore diameter is the average pore diameter after BJH adsorption

[0106] Table 3 shows the BET specific surface area, pore size distribution and pore volume of the two samples obtained based on the BET test results. It can be seen from the table that the BET specific surface area of ​​PdRu@SiO2 is 82.4 m 2 / g, pore volume is 0.08cm 3 / g, and the average pore size is about 7.58nm. The BET specific surface area of ​​PdRu / C@SiO2 is 172.4m 2 / g, pore volume is 0.13cm 3 / g, and the average pore size is about 4.68nm. It can be seen that high-temperature carbonization reduction can significantly increase the specific surface area of ​​PdRu / C@SiO2, provide more active sites, and thus enhance the catalytic activity.

[0107] Figure 6 FT-IR images of PdRu@ZIF-8@SiO2, PdRu@SiO2 and PdRu / C@SiO2 prepared in Example 1 show that PdRu@ZIF-8@SiO2, PdRu@SiO2 and PdRu / C@SiO2 have similar absorption peaks. However, the characteristic peak of Si-O-Si band appears at 800-1108cm -1 This again proves the existence of SiO2 shell. In addition, the characteristic peak of N / C band appears at 1596cm -1 And compared with PdRu@ZIF-8@SiO2 and PdRu@SiO2, the peak fluctuation of PdRu / C@SiO2 is smaller, which proves that it is a good carbon-nitrogen doped material.

[0108] Example 3 Catalytic performance test of different catalysts and optimization of reaction conditions

[0109] Catalyst performance evaluation method

[0110] In the present invention, the performance evaluation of the catalyst selective catalytic hydrogenation reaction is carried out by the reaction of phenylacetylene in a high-pressure reactor. A quantitative substrate, catalyst and solvent are added to a 35mL high-pressure reactor and sealed, and the H2 atmosphere is replaced five times. After the air in the reactor is almost completely discharged, H2 is introduced to make the pressure in the reactor 1.0MPa, so as to detect the selective hydrogenation performance of the catalyst. Under stirring at 500rpm, the timing is started after the reactor reaches and stabilizes at a predetermined temperature. After the reaction time is completed, it is immediately cooled, the residual gas in the reactor is discharged, the high-pressure reactor is opened, and the catalyst is filtered and clear liquid is taken.

[0111] Reaction product analysis method

[0112] The quantitative analysis of the liquid product was performed using a 7890B gas chromatograph (FID detector, SE-30 capillary column (30m×0.32mm, film thickness 0.25mm), with nonane as the internal standard). The injection port temperature was maintained at 250°C during the detection, the initial temperature of the column box was 100°C and maintained for 1 min, then the temperature was raised to 250°C after 7.5 min according to the predetermined program, and maintained at 250°C for 1 min. The qualitative analysis of the liquid product was performed using a gas chromatography-mass spectrometer. The conversion rate and selectivity were calculated according to the following formula:

[0113]

[0114] 3.1 Catalyst screening

[0115] According to the above method, different catalysts were placed under the same conditions for the selective catalytic hydrogenation reaction of phenylacetylene. The relevant catalysts were screened and optimized by analyzing the composition of the final reaction product. The reaction conditions were as follows: 5 mL ethanol (solvent), 53 μL phenylacetylene, 5 mg catalyst, reaction temperature 65 ° C, reaction pressure 1 MPa, reaction time 2 h.

[0116] The final results are shown in Table 3.1. The traditional Pd nanocatalyst (Pd@SiO2) has relatively high activity, but relatively low selectivity, and the Ru nanocatalyst (Ru@SiO2) has high selectivity, but low activity. Therefore, in this embodiment, an appropriate amount of Ru is added to the original Pd nanocatalyst to improve the selectivity.

[0117] Table 3.1 Screening results of catalytic hydrogenation performance of different catalysts

[0118]

[0119] Research on metal-carbon-based materials [7] It shows that the presence of carbon components can significantly enhance the dispersibility and stability of the metal components of the catalyst. In addition, the introduction of carbon components can significantly improve the molecular conductivity and accelerate the transfer of electrons during the reaction, thereby improving the catalytic performance of the catalyst. In the two catalysts prepared in this embodiment, the carbon component content in the catalyst PdRu@SiO2 is relatively low, while the catalyst PdRu / C@SiO2 has a relatively high carbon component content and forms a certain metal organic framework, so it should maintain better catalytic hydrogenation performance. The final catalytic hydrogenation performance screening results are also the same, and the catalyst PdRu / C@SiO2 is obtained. Under the same conditions, the conversion rate is 95.3% and the selectivity is 99.4%.

[0120] 3.2 Optimization of reaction conditions

[0121] In this embodiment, a series of optimization operations were performed on PdRu / C@SiO2, which had the best catalytic effect, including reaction solvent, reaction temperature, and reaction pressure, and finally the best reaction conditions were obtained.

[0122] The reaction solvent has a great influence on the performance of the selective catalytic hydrogenation of phenylacetylene. Figure 7 As shown in the figure (reaction conditions: 5mL solvent, 53μL phenylacetylene, 5mg catalyst, 65℃, 1MPa, 2h), the reaction results show that when the solvent is ethanol (EtOH), the conversion rate of phenylacetylene is 95.3% and the conversion rate is 99.4%; when the solvent is methanol (MeOH), the conversion rate of phenylacetylene is 88.2%, but the selectivity is reduced to 90.1%; when the solvent is tetrahydrofuran (THF), the conversion rate of phenylacetylene is 100.0%, but the selectivity is only 29.7%; when the solvent is cyclohexane (CHX), the conversion rate of phenylacetylene is 87.5% and the selectivity is 39.7%; when the solvent is 1,4-dioxane (1,4Dioxane), the conversion rate of phenylacetylene is 99.1%, but the selectivity is only 37.8%. Therefore, considering comprehensively, when ethanol is used as the solvent, the activity of the catalyst is the best.

[0123] Secondly, the effect of reaction temperature on the performance of selective catalytic hydrogenation of phenylacetylene was studied. Figure 8 As shown (reaction conditions: 5mL ethanol, 53μL phenylacetylene, 5mg catalyst, 1MPa, 2h). When the temperature is 25℃, the conversion rate of phenylacetylene is 24.9% and the selectivity is 100%; when the temperature is 45℃, the conversion rate of phenylacetylene is only 47.1% and the selectivity is 100%; when the temperature is 65℃, the conversion rate of phenylacetylene is increased to 95.3% and the conversion rate is 99.4%; when the temperature is 85℃, the conversion rate is increased to 100%, but the selectivity is reduced; when the temperature is 105℃, the conversion rate is still 100%, but the selectivity is still low. Obviously, at 65℃, the catalyst activity is the best, so 65℃ is selected as the optimal reaction temperature for the catalyst's selective catalytic hydrogenation performance of phenylacetylene.

[0124] Finally, this example studies the effect of reaction pressure on the performance of selective catalytic hydrogenation of phenylacetylene. Fig. 9The reaction conditions shown are: 5mL ethanol, 53μL phenylacetylene, 5mg catalyst, 65℃, 2h. When the pressure is 0.1MPa, the conversion rate of phenylacetylene is 32.6% and the selectivity is 100%; when the pressure is 0.5MPa, the conversion rate of phenylacetylene is 67.3% and the selectivity is 100%; when the temperature is 1.0MPa, the conversion rate of phenylacetylene increases to 95.3% and the conversion rate is 99.4%; when the pressure is 1.5MPa, the conversion rate increases to 100%, but the selectivity decreases; when the pressure is 2.0MPa, the conversion rate is still 100%, but the selectivity is lower. Obviously, at 1.0MPa, the catalyst activity is the best, so 1.0MPa is selected as the optimal reaction pressure for the catalyst's selective catalytic hydrogenation performance of phenylacetylene.

[0125] Figure 7-Figure 9 , and subsequent Fig.10 In the above, PA Conv. represents the conversion of phenylacetylene, SM Sel. represents the selectivity of styrene, and EB Sel. represents the selectivity of ethylbenzene.

[0126] The present invention prepares a synergistic catalytic system with Pd-Ru as active components, and after being coated with silicon, hybridized with nitrogen atoms, it is used for the directional catalytic semi-hydrogenation of phenylacetylene to styrene; the present invention applies the Pd-Ru synergistic catalytic system to the catalytic hydrogenation process of phenylacetylene, and while maintaining a high conversion rate, the selectivity for styrene is greatly improved. This catalytic activity is attributed to the synergistic effect of the Pd-Ru single point, which reduces the desorption energy of styrene and thereby increases the barrier for further hydrogenation of styrene, making it possible to apply the Pd-Ru synergistic catalytic system to the hydrogenation of phenylacetylene.

[0127] Example 4 Stability Analysis Experiment

[0128] Repeatability and stability are important results in evaluating catalyst performance. Therefore, this example conducted a cyclic application experiment on the PdRu / C@SiO2 catalyst. Fig.10 As shown in the figure (reaction conditions: 5 mL ethanol, 53 μL phenylacetylene, 5 mg catalyst, 65°C, 1 MPa, 2 h). It can be seen that in multiple reactions, the conversion rate of phenylacetylene can reach up to 96.1% at the highest and 95.3% at the lowest; its selectivity is always maintained at around 98.9%, which shows that the catalyst has considerable repeatability and stability.

[0129] Reaction time is also an important factor affecting catalyst performance. This example then studies the effect of reaction time on catalytic performance of the catalyst after the cycle application experiment. The reaction results are as follows: Fig.11As shown in the figure (reaction conditions: 5mL ethanol, 53μL phenylacetylene, 5mg catalyst, 65℃, 1MPa), when the reaction is 0.5h, the conversion rate of phenylacetylene is 33.7% and the selectivity is 100%; when the reaction is 1.0h, the conversion rate of phenylacetylene is 57.9% and the selectivity does not change; when the reaction is 1.5h, the conversion rate of phenylacetylene is 83.8% and the selectivity does not change; when the reaction is 2.0h, the conversion rate is increased to 95.3% and the selectivity is 99.4%; when the reaction is 2.5h, the conversion rate of phenylacetylene is 100%, but the selectivity is reduced to 92.7%. At multiple time points sampled in this embodiment, with the extension of reaction time, the conversion rate of phenylacetylene increases, but the selectivity decreases. Therefore, the catalyst still has quite good stability after the cyclic application experiment, and still maintains a high conversion rate and good selectivity after 2.0h of reaction.

[0130] Example 5 Universality Experiment of Catalyst

[0131] For catalysts, universality is also one of the key performances for evaluating the quality of catalysts. Therefore, this example explores the substrate range of PdRu / C@SiO2, and can only be selected within the range of substrates with high conversion rate (up to 85%) and good selectivity (up to 80%). The catalytic hydrogenation data of different phenylacetylene compounds on PdRu / C@SiO2 are summarized, and the specific results are shown in Table 5.1. The catalytic performance conversion rate of the hydrogenation reaction of methylphenylacetylene substrates (2-ethynyltoluene, 3-ethynyltoluene, 4-ethynyltoluene) in Table 5.1 is higher than 87%, and the selectivity of the corresponding target product methylstyrene reaches more than 80%, among which the selectivity of 2-ethynyltoluene is only 82.9%, which may be related to the structure of the substrate. In addition, the conversion rate of 4-methoxyphenylacetylene, 4-ethynylaniline, and 4-ethylphenylacetylene all reached 100%, and the selectivity also reached 80%; while 4-ethynylnitrobenzene required more stringent reaction conditions, the conversion rate reached 100%, and its selectivity was also good, at 96.4%; finally, the reaction conditions for 4-fluorophenylacetylene, 4-chlorophenylacetylene, and 4-bromophenylacetylene became more and more stringent, and their conversion rates all reached more than 90%, and their selectivity for the target product also reached more than 80%. It can be concluded that PdRu / C@SiO2 has a wide range of adaptability to the hydrogenation reactions of various phenylacetylene compounds.

[0132] Table 5.1 Substrate expansion of the selective hydrogenation of phenylacetylene compounds catalyzed by PdRu / C@SiO2

[0133]

[0134]

[0135] Note:

[0136] aReaction conditions: 5 mL ethanol, 0.05 mmol substrate, 5 mg catalyst, 105 °C, 1 MPa;

[0137] b Reaction conditions: 5 mL ethanol, 0.05 mmol substrate, 5 mg catalyst, 65 °C, 1 MPa;

[0138] c Reaction conditions: 5 mL ethanol, 0.05 mmol substrate, 5 mg catalyst, 35 °C, 1 MPa;

[0139] d Reaction conditions: 5 mL ethanol, 0.05 mmol substrate, 5 mg catalyst, 85 °C, 1 MPa.

[0140] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a Pd-Ru synergistic catalyst based on a metal organic framework, characterized in that: The following steps are involved: S1. Preparation of Pd-Ru@ZIF-8: Pd 2+ 、Ru 3+ 、Zn 2+ , 2-methylimidazole in a solvent, stirred for reaction, centrifuged after the reaction was completed, and the solid product was collected to obtain Pd-Ru@ZIF-8; S2, coating Pd-Ru@ZIF-8 with silicon dioxide to prepare PdRu@ZIF-8@SiO2; S3, carbonization reduction to prepare PdRu / C@SiO2, that is, the Pd-Ru synergistic catalyst based on the metal organic framework.

2. The method for preparing a Pd-Ru synergistic catalyst based on a metal organic framework according to claim 1, characterized in that: Step S1 is specifically as follows: S1-1, add 2.5-10 mg Pd(Acac)2 and 17.5-70 mg Ru(Acac)3 into 10-50 mL of a methanol mixed solution containing 280-1120 mg Zn(NO3)2·6H2O, mix well, and obtain a mixed solution A; S1-2, adding 263-1052 mg of 2-methylimidazole to 10-50 mL of methanol, and dispersing by ultrasonication to obtain a mixed solution B; S1-3. Add mixed solution B to mixed solution A, and stir to react for 12-48 hours. After the reaction is completed, collect the solid product by centrifugation, wash with methanol, and dry to constant weight to obtain Pd-Ru@ZIF-8.

3. The method for preparing a Pd-Ru synergistic catalyst based on a metal organic framework according to claim 1, characterized in that: Step S2 is specifically as follows: Take the Pd-Ru@ZIF-8 prepared in step S1 and add it to the ethanol aqueous solution, mix it evenly, add ammonia water, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate in sequence, stir to react, after the reaction is completed, centrifuge and wash the product, collect the solid product, dry to constant weight, and grind to obtain PdRu@ZIF-8@SiO2.

4. The method for preparing a Pd-Ru synergistic catalyst based on a metal organic framework according to claim 3, characterized in that: Step S2 is specifically as follows: Take 10-40g of Pd-Ru@ZIF-8 prepared in step S1 and add it to 10-40mL of ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, mix well, add 0.5-2mL of ammonia water with a mass concentration of 25%-28%, and then add 250-1000mg of hexadecyltrimethylammonium bromide. After it is completely dissolved, add 25-100μL of tetraethyl orthosilicate, stir and react for 6-24h, wash the product with ethanol solution by centrifugation, collect the solid product, dry it at 50-70℃ to constant weight, grind it, and obtain PdRu@ZIF-8@SiO2.

5. The method for preparing a Pd-Ru synergistic catalyst based on a metal organic framework according to claim 1, characterized in that: Step S3 is specifically as follows: Under a nitrogen atmosphere, the PdRu@ZIF-8@SiO2 prepared in step S2 is first calcined at 200-300°C for 240-960min, then heated to 500-700°C, calcined and reduced at 500-700°C for 90-360min, and cooled to room temperature to obtain PdRu / C@SiO2, i.e., the Pd-Ru synergistic catalyst based on the metal organic framework.

6. The method for preparing a Pd-Ru synergistic catalyst based on a metal organic framework according to claim 1, characterized in that: The following steps are involved: S1. Preparation of Pd-Ru@ZIF-8: S1-1, add 5 mg Pd(Acac)2 and 35 mg Ru(Acac)3 into 25 mL methanol mixed solution containing 560 mg Zn(NO3)2·6H2O, mix well, and obtain mixed solution A; S1-2, adding 526 mg of 2-methylimidazole into 25 mL of methanol, and dispersing by ultrasonication to obtain a mixed solution B; S1-3, adding mixed solution B to mixed solution A, stirring and reacting for 24 hours, after the reaction is completed, collecting the solid product by centrifugation, washing with methanol, drying to constant weight at room temperature, and grinding to obtain Pd-Ru@ZIF-8; S2. Pd-Ru@ZIF-8 is coated with silicon dioxide to prepare PdRu@ZIF-8@SiO2: Take 20g of the Pd-Ru@ZIF-8 prepared in step S1 and add it to 20mL of an ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, mix well, add 1mL of 25% ammonia water, then add 500mg of hexadecyltrimethylammonium bromide, add 50μL of tetraethyl orthosilicate after it is completely dissolved, stir at room temperature for 12h, wash the product with an ethanol solution by centrifugation, collect the solid product, dry it at 60°C to constant weight, grind it, and obtain PdRu@ZIF-8@SiO2; S3, carbonization reduction to prepare PdRu / C@SiO2: Under a nitrogen atmosphere, the PdRu@ZIF-8@SiO2 prepared in step S2 was first calcined at 250°C for 480 min, then heated to 600°C, calcined and reduced at 600°C for 180 min, and cooled to room temperature to obtain PdRu / C@SiO2, i.e., the Pd-Ru synergistic catalyst based on the metal organic framework.

7. A Pd-Ru synergistic catalyst based on a metal organic framework, characterized in that: It is prepared by the method according to any one of claims 1 to 6.

8. Use of the Pd-Ru synergistic catalyst as claimed in claim 7 in the selective hydrogenation of alkynes to produce olefins.

9. The use according to claim 8, characterized in that: in, The alkyne is any one of phenylacetylene, 2-ethynyltoluene, 3-ethynyltoluene, 4-ethynyltoluene, 4-methoxyphenylacetylene, 4-ethynylaniline, 4-ethylphenylacetylene, 4-ethynylnitrobenzene, 4-fluorophenylacetylene, 4-chlorophenylacetylene, and 4-bromophenylacetylene.

10. The use according to claim 9, characterized in that: The application method is: Evenly mix alkyne, ethanol and Pd-Ru synergistic catalyst, react for 1-4 hours at 65-85°C and 0.5-2MPa in H2 atmosphere to prepare the corresponding olefin; Wherein, the mass ratio of alkyne:ethanol:Pd-Ru synergistic catalyst is 5-20:0.5-2:0.5-2.

Citation Information

Patent Citations

  • Ultra-stable acetylene selective hydrogenation catalyst as well as preparation method and application thereof

    CN114632545A

  • Reactor for vapor phase reaction, and method for producing methane or methanol

    JP2023080453A

  • Catalysts for hydrogenation of unsaturated hydrocarbons and preparations and uses thereof

    US20120071700A1